Pengaruh Konsentrasi Larutan Natrium Bisulfit Terhadap Karakteristik Manisan Pala Basah (Myristica fragrans Houtt) - Hendrawan, Hendrawan (Ma'soem University, 2024)
Since long ago nutmeg was a popular commodity with high economical value, especially as spices. Nutmeg fruit could be processed into candied nutmeg, as an effort of food diversification. Problem in candied nutmeg production was the browning reaction. After having peeled, the color of flesh will change brown. This condition can lower the quality of nutmeg as raw material in food industry. One of the methods can be applied to prevent the browning reaction is by soaking nutmeg flesh in sodium bisulfite solution. Research had been conducted to find out the effect of soaking nutmeg flesh in sodium bisulfite at Chemistry Laboratory Agriculture Faculty Ma’soem University. The objective of the research was to determine the right solution of sodium bisulfite to produce the finest characteristic of candied nutmeg. The experimental method was applied in this research with six treatments; 500 ppm (A), 750 ppm (B), 1000 ppm (C), 1200 ppm (D), 1500 ppm (E), dan 1750 ppm (F), and each of the treatments was repeated four times. Monitoring was held on total soluble solid, vitamin C, sulfite residue, and organoleptic test on color, aroma, flavor and texture. Statistic analysis used variance analysis and proceeded by Duncan's Multiple Range Test. Result of the research showed that sodium bisulfite solution gave a significant effect on total soluble solid, sulfite residue, color and aroma. Vice versa, sodium bisulfite solution had no effect on vitamin C, flavor and texture. The 1500 ppm of solution produce the finest characteristics of candied nutmeg.